Host-guest charge transfer for scalable single crystal epitaxy of a metal-organic framework - Mantel, Arthur; Stöger, Berthold; Prado-Roller, Alexander; Shiozawa, Hidetsugu (Communications materials, 2024)
Methods to grow large crystals provide the foundation for material science and technology. Here we demonstrate single crystal homoepitaxy of a metal-organic framework (MOF) built of zinc, acetate and terephthalate ions, that encapsulate arrays of octahedral zinc dimethyl sulfoxide (DMSO) complex cations within its one-dimensional (1D) channels. The three-dimensional framework is built of two-dimensional Zn-terephthalate square lattices interconnected by anionic acetate pillars through diatomic zinc nodes. The charge of the anionic framework is neutralized by the 1D arrays of Zn ( DMSO ) 6 2 + cations that fill every second 1D channel of the framework. It is demonstrated that the repeatable and scalable epitaxy allows square cuboids of this charge-transfer MOF to grow stepwise to sizes in the centimeter range. The continuous growth with no size limits can be attributed to the ionic nature of the anionic framework with cationic 1D molecular fillers. These findings pave the way for epitaxial growth of bulk crystals of MOFs.
Keywords: Organic-inorganic nanostructures